2023
DOI: 10.1101/2023.03.28.23287745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and feasibility of Pharmacoscopy-guided treatment for acute myeloid leukemia patients that exhausted all registered therapeutic options

Abstract: Elderly or unfit patients with relapsed acute myeloid leukemia (AML) face a poor prognosis and are likely to rapidly exhaust all registered treatment options. Pharmacoscopy, an image-based ex vivo drug screening platform, has previously been suggested as a tool for treatment selection in AML. We used pharmacoscopy to generate personalized treatment recommendations for 30 relapse settings of 24 AML patients which exhausted all standard therapeutic options. We evaluated whether pharmacoscopy can be employed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In previous clinical trials, PCY identified effective therapies for aggressive haematological malignancies [33][34][35]45,46 . To evaluate the use of pharmacoscopy in glioblastoma, we measured ex vivo drug responses to first-and second-line glioblastoma chemotherapies (n=3 drugs) in patient samples from two independent patient cohorts: our main prospective cohort (n=27 patients) and a retrospective cohort (n=18 patients, Fig.…”
Section: Therapeutically Targeting Neural Tumour Heterogeneitymentioning
confidence: 99%
“…In previous clinical trials, PCY identified effective therapies for aggressive haematological malignancies [33][34][35]45,46 . To evaluate the use of pharmacoscopy in glioblastoma, we measured ex vivo drug responses to first-and second-line glioblastoma chemotherapies (n=3 drugs) in patient samples from two independent patient cohorts: our main prospective cohort (n=27 patients) and a retrospective cohort (n=18 patients, Fig.…”
Section: Therapeutically Targeting Neural Tumour Heterogeneitymentioning
confidence: 99%